PET/CT imaging of bone disorders in dysparathyroidism: a comprehensive review - Panagiotidis, E.; Angelidis, G.; Valotassiou, V.; Tsougos, I.; Georgoulias, P.; Zhang-Yin, J. T. (Frontiers in Nuclear Medicine, 2025)
Parathyroid disorders profoundly affect bone metabolism, often long before structural damage is apparent on conventional imaging. Positron emission tomography/computed tomography (PET/CT) has emerged as a transformative tool in dysparathyroidism, enabling visualization of early metabolic bone changes and accurate localization of parathyroid pathology. This review explores the pathophysiology of bone disease in hyper- and hypoparathyroidism and highlights the role of key PET radiotracers: fluorine-18 sodium fluoride ([18F]NaF), fluorine-18 fluorodeoxyglucose ([18F]FDG), fluorine-18 fluorocholine ([18F]FCH), gallium-68 prostate-specific membrane antigen ([68Ga]PSMA). Distinct imaging patterns, such as the [18F]NaF “superscan” in secondary hyperparathyroidism and focal uptake in brown tumors, are discussed alongside tracer-specific strengths. Clinical applications including diagnosis, monitoring response to therapy, and prognostication are examined. We also consider emerging technologies such as artificial intelligence (AI)-assisted interpretation and positron emission tomography/magnetic resonance imaging (PET/MRI) fusion imaging. As PET/CT becomes more accessible, it is likely to play an increasingly central role in the early detection and personalized management of parathyroid-related bone disease.